The blacklisting mechanism: New-school regulation of online expression and its technological challenges - Liudmila Sivetc (Routledge, 2022)
This chapter hopes to throw some light onto the relationship of censorship, legality and technology in contemporary Russia. In a digital age, the Russian government regulates online free expression not only in an old-school manner by penalising illegal content post ante in the result of court proceedings, but also in a new-school way by penalising allegedly illegal content ex ante as the result of administrative procedures. This new-school regulation presupposes assistance from internet service providers, who block websites in accordance with notifications issued by Roskomnadzor. The practice of website blocking, referred as the blacklisting mechanism, is explained by analysing relevant legislation, case law and official statistics. The explanation leads to the conclusion that, although digital technologies have made it easier for the state to censor online content by website blocking, side-effects of this technology-enabled censorship have surpassed the intentions of the legislator. These side-effects – over-blocking and malicious blocking – may put the future of website blocking in doubt.
Freedom of Expression in Russia's New Mediasphere